Analisis pengaruh kreatifitas iklan, daya tarik iklan, dan kredibilitas endorser Terhadap brand attitude pada produk Nokia Asha di kota Pekanbaru - Rizal P Nasution; Lilis Sulistyowati; Marhadi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to determine the influence analysis advertising creativity, attractiveness and quality of advertising on brand attitude advertising messages on Brand Nokia Mobile Asha in Pekanbaru. Inside The study consisted of a bound variable is the attitude of consumers (Y), and three independent variables consisting of kreatifitasiklan (X1), advertising appeal (X2), and the credibility of the endorser (X3). Study using purposive sampling technique . Population of this study is the Pekanbaru with a sample of 100 respondents . Who has a Nokia mobile phone and or have seen ads on TV Mobile Nokia Asha . Analysis of research data using qualitative methods , quantitative and multiple regression equations with the help of SPSS ( Statistic Services For Product and Solution ) .From the results of this study showed that , Brand Attitude on Mobile Nokia Asha in Pekanbaru is positive can be seen from the calculation of average have a positive value except for the appeal is negative , but overall the three variables have a significant effect .Keywords: Brand Attitudes, Creativity in Advertising, Fascination Advertising, Endorser Credibility.